2017
DOI: 10.1177/0004867417720516
|View full text |Cite
|
Sign up to set email alerts
|

Use of granulocyte-colony stimulating factor to prevent recurrent clozapine-induced neutropenia on drug rechallenge: A systematic review of the literature and clinical recommendations

Abstract: Background: Clozapine is the most effective medication for treatment-refractory schizophrenia; however, its use is contraindicated in people who have had previous clozapine-induced neutropenia. Co-prescription of granulocyte-colony stimulating factor may prevent recurrent neutropenia and allow continuation or rechallenge of clozapine.Objective and methods: Systematic review of literature reporting the use of granulocyte-colony stimulating factor to allow rechallenge or continuation of clozapine in people with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 50 publications
1
44
3
1
Order By: Relevance
“…Prescribers in countries without local monitoring guidelines should refer to schedules recommended by the registries of countries with similar ethnic composition, given the differences between ethnicities in monitoring requirements. In the event of decreasing absolute neutrophil counts, local registry guidelines as to the threshold for which holding clozapine is required should be followed, and if appropriate, the use of lithium or granulocyte colony‐stimulating factor , both of which stimulate the generation of granulocytes in the bone marrow, should be considered. Persistence or progression of low neutrophil after interruption of clozapine treatment should prompt a hematology consult.…”
Section: From Research To Clinical Practice: When and How To Prescribmentioning
confidence: 99%
“…Prescribers in countries without local monitoring guidelines should refer to schedules recommended by the registries of countries with similar ethnic composition, given the differences between ethnicities in monitoring requirements. In the event of decreasing absolute neutrophil counts, local registry guidelines as to the threshold for which holding clozapine is required should be followed, and if appropriate, the use of lithium or granulocyte colony‐stimulating factor , both of which stimulate the generation of granulocytes in the bone marrow, should be considered. Persistence or progression of low neutrophil after interruption of clozapine treatment should prompt a hematology consult.…”
Section: From Research To Clinical Practice: When and How To Prescribmentioning
confidence: 99%
“…Two strategies commonly employed to manage clozapine-associated neutropenia are the use of lithium (Paton and Esop, 2005) and Granulocyte Colony-Stimulating Factor (G-CSF) (Lally et al, 2017;Myles et al, 2017). These strategies are not without risks.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that filgrastim can be used with lithium to induce neutrophilia in patients with clozapine-induced neutropenia [ 12 ]. Filgrastim works most effectively when prescribed prophylactically [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that filgrastim can be used with lithium to induce neutrophilia in patients with clozapine-induced neutropenia [ 12 ]. Filgrastim works most effectively when prescribed prophylactically [ 12 ]. It is important that hematology specialists are involved, patient education is advocated, and blood monitoring is adhered to in utilizing such strategies to avoid neutropenia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation